Low testosterone in non-responsive coeliac disease: A case series, case–control study with comparisons to the National Health and Nutrition Examination Survey. Issue 10 (October 2016) - Kurada, Satya; Veeraraghavan, Gopal; Kaswala, Dharmesh; Hansen, Josh; Cohen, David; Kelly, Ciaran; Leffler, Daniel
Abstract: Background: Adults with coeliac disease (CD) often report persistent fatigue, even when CD appears well controlled for unknown reasons. Aims: To evaluate common indications for testosterone panel (TP) testing and prevalence of low testosterone (T) in CD. Methods: In our case series, we determined common indications for checking TP in CD. Next, we conducted a case–control study to compare TP in CD vs. healthy controls (HC). We compared mean total T (TT), free T (FT) based on serologic, histologic disease activity. Finally, we assessed TT in tissue transglutaminase (tTG)+ vs. tTG− subjects and CD vs. HC obtained from the National Health and Nutrition Examination Survey (NHANES). Results: 53 coeliac males had TP tested. Common indications included osteoporosis and fatigue. Low FT was observed in 7/13 men with osteoporosis and 5/6 with fatigue. In our case–control study ( n  = 26 each), there was no difference in mean TT or FT between CD vs. HC, tTG+ vs tTG− or Marsh 0 vs. Marsh 3 groups. NHANES data showed no difference in mean TT between tTG+ vs tTG− ( n  = 16 each) or CD vs. HC subjects ( n  = 5 each). Conclusions: Low T occurs in CD patients at a similar rate as the general population. Common presentations of low T may mimic non-responsive CD symptoms.